Locoregional recurrences after transanal total mesorectal excision of rectal cancer during implementation. Issue 9 (4th April 2020) - Oostendorp, S E; Belgers, H J; Bootsma, B T; Hol, J C; Belt, E J T H; Bleeker, W; Den Boer, F C; Demirkiran, A; Dunker, M S; Fabry, H F J; Graaf, E J R; Knol, J J; et al.
Abstract: Background: Transanal total mesorectal excision (TaTME) has been proposed as an approach in patients with mid and low rectal cancer. The TaTME procedure has been introduced in the Netherlands in a structured training pathway, including proctoring. This study evaluated the local recurrence rate during the implementation phase of TaTME. Methods: Oncological outcomes of the first ten TaTME procedures in each of 12 participating centres were collected as part of an external audit of procedure implementation. Data collected from a cohort of patients treated over a prolonged period in four centres were also collected to analyse learning curve effects. The primary outcome was the presence of locoregional recurrence. Results: The implementation cohort of 120 patients had a median follow up of 21·9 months. Short-term outcomes included a positive circumferential resection margin rate of 5·0 per cent and anastomotic leakage rate of 17 per cent. The overall local recurrence rate in the implementation cohort was 10·0 per cent (12 of 120), with a mean(s.d.) interval to recurrence of 15·2(7·0) months. Multifocal local recurrence was present in eight of 12 patients. In the prolonged cohort (266 patients), the overall recurrence rate was 5·6 per cent (4·0 per cent after excluding the first 10 procedures at each centre). Conclusion: TaTME was associated with a multifocal local recurrence rate that may be related to suboptimal execution rather than the technique itself. Prolonged proctoring, optimization of the technique to avoid spillage, and quality control is recommended. Graphical Abstract: During the learning curve, the transanal total mesorectal excision procedure is associated with a high multifocal local recurrence rate, which appears to be related to suboptimal execution rather than the technique, and necessitates prolonged proctoring, optimization of the technique avoiding spillage, participation in controlled clinical trials with surgical quality control, and centralization until oncological safety is demonstrated. Defines a learning curve